USAHA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KENAKALAN REMAJA PADA KELAS X SMK NEGERI 1 BARABAI KABUPATEN HULU SUNGAI TENGAH - Achmad Fauzi (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2018)
The purpose of this research is to know the effort of conseling guidance teacher for eclipse adolescense mischief of student of X SMK Negeri 1 Barabai Hulu Sungah Tengah. The sample of this research is class X A AP 35 students with consideration that many of student at class XA AP make eclipse adoleslense. The research method of this research is description method. based on the research, than the conclusion in many students at class X A explain that the counseling guidance teacher always give them advice and eclipse adolescense mischief of class X SMK Negeri 1 Barabai Hulu Sungai Tengah Regency. This matter show that thecounseling guidance teacher and all part of school always be running a business in a maximal quality for eclipse adoleslense mischief ( their student) until they can substract in fact deleted the negative image of that school.